Assistance in Preparing Craft Learning Implementation Plans Based on the Use of Local Food to Prevent Anemia in Gorontalo Regency: Pendampingan Penyusunan Rencana Pelaksanaan Pembelajaran Prakarya Berbasis Pemanfaatan Pangan Lokal Cegah Anemia di Kabupaten Gorontalo - Margaretha Solang; Muh. Nur Akbar; Syam S. Kumaji; Yuliana Retnowati; Vivien Novariana; Asniawati Zainuddin; Budy Santosa; Eman Rahim; Muhammad Isra (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Anemia in adolescents is one of the factors that cause stunting, and it has impacted the educational system. It is important for students to be knowledge and skills equipped necessary to overcome the anemia problem independently in order to improve the quality of their education. The various programs that have been launched by the government are still not being implemented optimally because there are still some teachers who do not have the knowledge to develop learning plans that lead to the use of local food to prevent anemia in the Gorontalo Regency. To address this issue, it is necessary to implement innovative learning methods so that students receive education and skills through the processing of local food in order to prevent anemia, which is possible through the study of craft subjects. This assistance is intended to assist in the preparation of lesson plans (RPP) based on local food processing in order to prevent anemia. This activity is directed at Prakarya teachers in 5 Senior High Schools in the Gorontalo Regency. In this case, workshops and mentoring were used as methods. Workshops and mentoring were carried out face to face which focus on developing lesson plans based on discovery learning and project-based learning. The results of this activity are skills in preparing lesson plans based on the use of local food to prevent anemia by Prakarya teachers in Gorontalo Regency. This lesson plans will then be implemented in the odd semester of the 2023/2024 academic year.